Pencegahan Konflik Pembangunan Desa: Perspektif Undang-Undang Nomor 3 Tahun 2024 Tentang Desa - Sihombing, Desi Natalia; Djayeng Tirto; Arifuddin Uksan (Ministry of Home Affairs, 2025)
Village development is one of the main pillars in the effort to improve community welfare and promote economic equity. Although the number of advanced and self-sufficient villages has continued to increase, the gap between rural and urban areas remains significant, particularly in infrastructure, access to basic services, and technology. Development conflicts are largely unavoidable, often triggered by disparities in resource distribution, ineffective communication, and limited public understanding of development benefits. This study examines the role of village autonomy in preventing development conflicts and its implications for sustainable and equitable growth, using Wadas Village, Central Java, as a case study. The conflict emerged from the government’s plan to exploit andesite stone for the Bener Dam without transparent public participation. The local community resisted, fearing environmental degradation and threats to agricultural land. The unequal distribution of benefits intensified tensions, as residents perceived more harm than advantage from the project. This study employed a descriptive-analytical method with a qualitative approach to analyze conflict patterns and contributing factors by reviewing academic literature, policy reports, and official documents. The findings reveal that village development conflicts in Indonesia are multidimensional, shaped by socio-economic disparities and uneven resource distribution. Poor communication, limited public participation, and neglect of local wisdom further exacerbate tensions. Village autonomy offers a strategic opportunity to establish conflict prevention mechanisms through policy integration. A holistic approach, encompassing structural assessment, actor analysis, and conflict mitigation, can foster more inclusive and equitable development.